Multipartite Disentanglement Dynamics Due Simultaneously to Amplitude Damping and Phase Damping - An, Nguyen Ba (Communications in Physics, 2009)
We present a detailed analysis on disentanglement dynamics of multiqubit GHZ-type states whose qubits are remotely located in absence of any mutual interactions. The dynamics is thus induced by independent local environments surrounding each qubit. It has recently been known that if each qubit is subjected solely to the phase damping then the state's entanglement vanishes asymptotically in time and if only the amplitude damping is active then the state's entanglement may vanish suddenly in certain parameter subspace. In this paper, we shall show that a combined action of both the phase damping and the amplitude damping will force the state's entanglement to always vanish suddenly in the entire parameter space. Furthermore, we shall prove that by proper local operations such a finite-time disentanglement can be avoided for whatever state's parameters, no matter the phase damping and the amplitude damping act severally or in combination